'Luigi Nono: Resonances' Summer School 2024 - Parra Cancino, Juan; 'Luigi Nono: Resonances' Sumer School 2024 Orpheus Institute July 2-8, 2024 (2024)
Several courses focused on Luigi Nono's reperotire, through the lens of instrumental practices (piano, violin, flute), compositional practices and Electronic practices.
Summer school organised by a group of Orpheus Researchers, around the figure and work of Luigi Nono
FRIS
Editorial review
Keywords: Music, Thought and Technology